DAMPAK SIKLUS OPERASI,ARUS KAS OPERASI , DAN FEE AUDIT TERHADAP PERSISTENSI LABA - Putri Meliyansyah; Wibowo, Agus Satrya; Setiawan, Ricky Yunisar (Jurnal Riset Akuntansi, 2024)
This study examines how operational cash flow, audit fees, and the operating cycle affect the longevity of profitability in real estate and property businesses listed on the IDX between 2022 and 2023. Regression research based on financial statement data and quantitative approaches showed that audit fees have no discernible impact on earnings persistence, while operational cash flow and the operating cycle do. Maintaining steady profitability is frequently difficult for businesses with lengthy operational cycles and erratic operating cash flows. This study offers insightful information on the variables affecting earnings persistence in the real estate and property industry, emphasising the importance of operational efficiency and effective cash flow management for stable financial performance.